Spatial variability of CO2 concentrations and biogeochemistry in the Lower Columbia River. Issue 4 (2nd October 2017) - Crawford, John T.; Butman, David E.; Loken, Luke C.; Stadler, Philipp; Kuhn, Catherine; Striegl, Robert G.
Abstract: Carbon dioxide (CO2 ) emissions from rivers and other inland waters are thought to be a major component of regional and global carbon cycling. In large managed rivers such as the Columbia River, contemporary ecosystem changes such as damming, nutrient enrichment, and increased water residence times may lead to reduced CO2 concentrations (and emissions) due to increased primary production, as has been shown in another large North American river (Upper Mississippi). In this work, spatial patterns of water quality, including dissolved CO2 concentrations, were assessed in the Lower Columbia River (LCR) and major tributaries using underway measurements from a small research vessel during July 2016. We observed near-equilibrium CO2 conditions and overall weak supersaturation of CO2 in the main channel (average 133.8% saturation) and tributaries. We observed only weak correlations between CO2 saturation, chlorophyll a fluorescence, and turbidity, thus not strongly supporting our hypothesis of primary productivity controls. In general, the LCR was clear (low turbidity, mean = 1.48 FNU) and had low chlorophyll fluorescence (mean = 0.177 RFU) during the sampling period. As a whole, the LCR was homogeneous with respect to biogeochemical conditions and showed low spatial variability at >100 km scales. Overall, we find that the LCR is likely a weak summertime source of CO2 to the atmosphere, in line with findings from other altered rivers such as the Upper Mississippi.